O Novo Relatório do Auditor Independente (NRA) - Alves, Aline Thatyana Aranda da Rocha Branco Alcantara (2019)
Since December 2016, the Independent Auditor's New Report (NRA) has been in effect, created due to investor demand for more information on the auditor's work. After three years of new reports issued, the need arises to identify whether these reports demonstrate that the objectives that motivated their creation were met, that is, if more information, customization and clarity were presented. To this end, this research was conducted using quali-quanti analyzes through careful reading of the standards that created the NRA and exploratory documentary study of the independent auditor's reports regarding the financial statements from 2016 to 2018. Analyzing their structures, customizations and readability. Key Audit Matters (PAAs) and the types of reports issued were also identified. For readability analysis, the Flesch Reading Ease formula developed by Rudolf Flesch was used. The analyzed companies were the winners of the Transparency Trophy of 2017 and 2018 participants from the same segments. The results showed that the reporting frameworks were 100% compliant with NBC TA 700, the reports averaged 3 PAAs per report issued, some reports were standardized rather than customized, and the 100% readability of the reports is below 30, i.e., very difficult, with readability for users with at least complete graduation. Thus it can be observed that some items that motivated the creation of the NRA were answered as: more transparency and information through the PAAs. And others have not yet been fully met, such as: customization and clarity